Anterior Segment Ischemia After Peripheral Annular Lamellar Sclerokeratoplasty for Advanced Terrien Marginal Degeneration. Issue 6 (June 2021) - Mudgil, Tanvi; Fernandes, Merle
Abstract : Abstract: A man with 360° bilateral peripheral thinning, peripheral vascularization, and lipid deposition diagnosed with Terrien marginal degeneration, underwent a 360° peripheral annular lamellar sclerokeratoplasty (PALK) (tuck-in) in the right eye for 90% peripheral thinning and high astigmatism. One-week postoperatively, a sudden drop in vision to counting fingers 1 m from 20/50 with circumciliary congestion, diffuse corneal edema, intense anterior chamber inflammation, keratic precipitates with fixed dilated pupil, and hypotony led to a diagnosis of suspected anterior segment ischemia. Anterior segment fluorescein angiography was suggestive of ischemia. After intensive topical and systemic steroids tapered over 6 months, his symptoms and signs improved. At the last follow-up 4 years later, his best contact lens-corrected visual acuity was 20/30. Anterior segment ischemia has not been reported after a PALK for advanced corneal ectatic disorders. Prompt diagnosis and commencement of intensive steroids was helpful in reversing this condition.